Flavonoids and Related Members of the Aromatic Polyketide Group in Human Health and Disease: Do They Really Work - Tauchen, Jan; Huml, Lukáš; Rimpelova, Silvie; Jurášek, Michal (Molecules, 2020)
Some aromatic polyketides such as dietary flavonoids have gained reputation as miraculous molecules with preeminent beneficial effects on human health, for example, as antioxidants. However, there is little conclusive evidence that dietary flavonoids provide significant leads for developing more effective drugs, as the majority appears to be of negligible medicinal importance. Some aromatic polyketides of limited distribution have shown more interesting medicinal properties and additional research should be focused on them. Combretastatins, analogues of phenoxodiol, hepatoactive kavalactones, and silymarin are showing a considerable promise in the advanced phases of clinical trials for the treatment of various pathologies. If their limitations such as adverse side effects, poor water solubility, and oral inactivity are successfully eliminated, they might be prime candidates for the development of more effective and in some case safer drugs. This review highlights some of the newer compounds, where they are in the new drug pipeline and how researchers are searching for additional likely candidates.
Keywords: Polyketides; antioxidancia; polyketidy; klinické zkoušky jako téma; Flavonoids; lidé; Antioxidants; flavonoidy; Humans; Clinical Trials as Topic